Women’s self-help groups as a delivery platform for nutrition and health interventions in India - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Findings were published in BMJ Global Health. Self-help or women’s groups are not a CGIAR innovation. The evidence on their effectiveness as a platform for delivering nutrition-sensitive interventions, particularly nutrition-sensitive agricultural interventions, is what makes this a relevant A4NH innovation for CGIAR.